Inovasi Buku Ajar Digital Berbasis Web untuk Meningkatkan Pembelajaran Bahasa Indonesia di Sekolah Dasar Awal - Shopiya, Shopiya; Wulandari, Pitri Dewi; Ningrum, Ayu Alya; Syabrina, Muhammad (IAIN Kendari, 2025)
This study aims to develop a website-based digital teaching material as an interactive learning medium for second-grade students at MIN 4 Palangka Raya in Indonesian language lessons focusing on traffic signs. Using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the study involved validation by subject matter experts, design experts, and teachers. Field trials were conducted on 19 second-grade students. Validation results showed high feasibility, with scores of 96.18% (subject matter experts), 96.99% (design experts), and 96.43% (teachers). Field trials demonstrated a significant improvement in student learning outcomes, with an N-Gain score of 0.73 (moderately effective) and an effectiveness rate of 94.61%. The teaching material effectively enhanced students' comprehension, engagement, and learning motivation. This research contributes theoretically to the development of technology-based teaching materials and offers practical solutions for innovative learning in the digital era. Recommendations for future research include developing similar teaching materials for other subjects and exploring Augmented Reality (AR) and Virtual Reality (VR) technologies.Keywords: Digital teaching materials, interactive learning, website, traffic signs.